2012
DOI: 10.1016/j.actbio.2012.03.046
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of aging to the fatigue crack growth resistance of human dentin

Abstract: An evaluation of the fatigue crack resistance of human dentin was conducted to identify the degree of degradation that arises with aging and the dependency on tubule orientation. Fatigue crack growth was achieved in specimens of coronal dentin through application of Mode I cyclic loading and over clinically relevant lengths (0 ≤ a ≤ 2 mm). The study considered two directions of cyclic crack growth in which the crack was either in-plane (0°) or perpendicular (90°) to the dentin tubules. Results showed that rega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
67
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(73 citation statements)
references
References 49 publications
3
67
0
Order By: Relevance
“…A recent micro-CT study showed significantly more dentinal defects in roots obtained from patients ranging from 40 to 71 years when compared to patients with an age range of 20-39 years old (PradeepKumar et al 2017). These results are in agreement with the findings of Ivancik et al that showed aging as a factor that reduces the resistance of coronal dentin (Ivancik et al 2012). …”
Section: Clinical Relevancesupporting
confidence: 82%
See 1 more Smart Citation
“…A recent micro-CT study showed significantly more dentinal defects in roots obtained from patients ranging from 40 to 71 years when compared to patients with an age range of 20-39 years old (PradeepKumar et al 2017). These results are in agreement with the findings of Ivancik et al that showed aging as a factor that reduces the resistance of coronal dentin (Ivancik et al 2012). …”
Section: Clinical Relevancesupporting
confidence: 82%
“…Several factors have been associated with ROF: age, parafunctional habits, overfilling, and poor restoration (Ivancik et al 2012;PradeepKumar et al 2016;Qiao et al 2017). Recently, the change in bite forces after root canal treatment has been shown and should be investigated further as a potential factor (Awawdeh et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In this approach, the "intrinsic" flaw size is estimated by equating the stress-life and fatigue crack growth responses for dentin. A value of 0.83 MPa•m 0.5 is used for the stress intensity threshold (Bajaj et al, 2006;Ivancik et al, 2012) and a value of unity for the geometry factor. The reduction in apparent endurance limit of dentin [ Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The notion that patient age influences VRF Time from Non-vitality to VRF and Age has been supported by several laboratory studies showing a reduction in fatigue strength and fracture resistance in dentin with age 2,3,[8][9][10]15) . Bajaj et al 3) showed that fatigue cracks in old dentin occurred at a lower stress intensity level than in young dentin and propagated at a significantly faster rate.…”
Section: Discussionmentioning
confidence: 78%
“…Non-vital teeth are more prone to VRF, a phenomenon which has been attributed to excessive force during obturation 7) , the wedging effect of spreaders during lateral condensation 11) , excessive pressure during post cementation 14,16) , a decrease in dentin thickness with finger-spreaders 22) , and post preparation 13,21) . On the other hand, several reports investigating extractions of caries-free teeth have revealed a reduction in fatigue strength and fracture resistance in dentin with age in laboratory tests 2,3,[8][9][10]15) . Furthermore, some studies have noted an increase in the frequency of VRFs in endodontically restored teeth in patients aged over 40 years 6,19,20,23) .…”
Section: Introductionmentioning
confidence: 99%